Retour sur la recherche à l’École nationale supérieure de paysage de Versailles-Marseille (1995-2011) - Pierre Donadieu (Projets de Paysage)
Through going back, notably, on some Ph.D research results led within the research lab of the ENSP of Versailles (LAREP) during the last 15 years, a part of the knowledge concerning the landscape project of the landscapers, and the societal and political projects of landscape, have been combined. In the field of social and human sciences, the study methods of the landscape project are evoked, and new research questions emerge.